Management of Bilateral Ankyloblepharon with Hay-Wells Syndrome: A Rare Case Report: Poster Presentation - Case Report - Resident - Junetta Airene Priskila Taba; Putu Yuliawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ankyloblepharon is a partial or complete fusion of the eyelid margins. This condition can be found as a common manifestation of Hay-Wells Syndrome along with lip and/or palate cleft and ectodermal dysplasia. This is an extremely rare case report demonstrating management of ankyloblepharon with Hay-Wells Syndrome. Case Illustration : A 5-day-old baby consulted from the Neonatal Intensive Care Unit (NICU) with multiple congenital abnormalities. The baby was born preterm (32 weeks) by C-section due to fetal malpresentation with low birth weight (1545 gram). There was no family history of congenital anomalies. Ocular examination revealed a partial ankyloblepharon on both eyes. The baby was also found with labiognatopalatoschizis, microtia, hyperkeratotic skin and nail dystrophy. Then, we planned to do an eyelid separation procedure at the NICU using only sterile conjunctival scissors with drops of Pantocaine 2%. Gentamicin eye ointment three times daily was prescribed. After the procedure, we can do a proper evaluation of the eye. Discussion : Hay-Wells Syndrome is a rare autosomal dominant disorder. This condition characterized by various congenital abnormalities such as ankyloblepharon, lip and/or palate cleft, and also other abnormalities involving the skin, hair, teeth, nails, and sweat glands. The management of ankyloblepharon can be done easily by excised the webs of skin that connecting the eyelid margins with topical anesthesia. The purpose of this management is mainly to prevent the risk of the development of deprivation amblyopia. Conclusion : Congenital ankyloblepharon has the potential to cause deprivation amblyopia. An immediate management is needed to provide a good prognosis regarding the visual development